1984
DOI: 10.1007/bf00342674
|View full text |Cite
|
Sign up to set email alerts
|

Ocular volume measured by CT scans

Abstract: Newer CT scans have greatly enhanced oculometric research and made it possible to measure ocular dimensions. With these measurements, ocular volume can be more accurately estimated to understand its relationship with age and sex. One hundred CT orbit scans with presumed normal eyes were used for the data base. The mean values and normal variations of ocular volumes at various ages in both sexes are presented. Rapid growth of the eyeball was noted during the first 24 months of age. It reached its peak between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 3 publications
3
28
0
Order By: Relevance
“…This is in contrast with the speculation of Ahmadi et al (22) that the orbital adipocytes undergo atrophy with advancing age. The significant correlation of age with TOFV may be attributable to a relative reduction in muscular bulk and volume of the globe itself with increasing age (23,24). In addition, Darcy et al (25) observed an increase in total orbital fat and periocular soft tissue with aging, which they claimed was due to fat expansion, which is consistent with the results of the present study, and which may be the rationale for fat excision from the eyelids in plastic and aesthetic surgery.…”
Section: Unstandardized Coefficients --------------------------------mentioning
confidence: 99%
“…This is in contrast with the speculation of Ahmadi et al (22) that the orbital adipocytes undergo atrophy with advancing age. The significant correlation of age with TOFV may be attributable to a relative reduction in muscular bulk and volume of the globe itself with increasing age (23,24). In addition, Darcy et al (25) observed an increase in total orbital fat and periocular soft tissue with aging, which they claimed was due to fat expansion, which is consistent with the results of the present study, and which may be the rationale for fat excision from the eyelids in plastic and aesthetic surgery.…”
Section: Unstandardized Coefficients --------------------------------mentioning
confidence: 99%
“…Further, Priestly [12] and Hahn and Chu [1] reported that the eyeball volume of young adult subjects was larger than that of older adults. The study on the change of the orbital size (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many studies have analyzed the relationships between orbital or eyeball volumes and age, gender, or race using computed tomography (CT) or magnetic resonance imaging (MRI) [1][2][3][4][5][6][7][8][9][10][11] . Comparing MRI and CT data, Chau et al [11] reported that orbital and eyeball volume measurements using MRI correlated with those acquired using CT and that MRI provided a more accurate result than CT.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophthalmus is said to be present when all dimensions of the eye are increased but glaucoma is not present (21 In previous studies measuring MRI and CT scanning, VE and VO were estimated using planimetry, but the coeffi cient of error was not calculated. Furthermore, none of these studies used stereological methods to estimate the volume (10)(11)(12)(13)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 99%